THE MAIN SPRING OF THE MACHINE. ITINERANT JAILS IN THE PORTALES REGIME. CHILE 1830-1840. - Rivera Tobar, Francisco (Revista de Historia Social y de las Mentalidades, 2011)
This article analyzes the “presidio ambulante” (itinerant jail) as one device of social disci - pline imposed by Chile’s conservative elites during the period of State consolidation that followed intra-elite struggles (1830-1840), highlighting the role of Minister Diego Portales. It explores critically the various functions of the “carros jaula” (cage carts), as well as the living conditions and resistance mechanisms displayed by the prison inmates vis-à-vis the authoritarian regime. The role of this disciplinary system on the eve of the war against the Confederacion Perú-Boliviana is also dealt with, including its links with the main economic processes of the early 19th Century. In sum, this study considerers the “presidio ambulante” as a reflection on the elite’s views regarding the role of the popular sectors in the making of a nation-state guided by the principles of republicanism.